Teaching and Learning Qualitative Methodologies in the Context of Developing Doctoral Education in Lithuania - Skukauskaitė, Audra; Rupšienė, Liudmila (Acta Paedagogica Vilnensia, 2017)
With the expansion of available research methodologies, particularly those in qualitative research, scholars began examining the various aspects of doctoral programs, including program design, student experiences and research writing. Recently, more researchers also started investigating research learning and teaching within doctoral programs. However, most of the literature on doctoral preparation is derived from the English-speaking world and research learning in non-English speaking countries remains invisible. To address this inequity, in this study, we examine the teaching and learning of qualitative research within a doctoral qualitative research methods class in Lithuania. In the article, we provide a historical context and present analyses from interviews with one doctoral student and two professors who taught the class. The study demonstrantes a strong potential of Lithuanian scholars to teach, learn and contribute to qualitative research internationally.